2017
DOI: 10.1017/jmo.2017.37
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of top management support on employees’ attitudes in response to human resource development efforts

Abstract: The purpose of this study is to investigate the relationships among human resource development (HRD) efforts, top management support, and employees’ attitudes (job satisfaction and organizational commitment) in the Korean context. Based on the Korean Human Capital Corporate Panel survey data, 3,899 responses from 159 large companies were analyzed by adopting hierarchical multiple regression analysis and a regression-based path analysis. The results indicated that HRD efforts positively affected organizational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 94 publications
(141 reference statements)
1
36
0
10
Order By: Relevance
“…However, this can be countered by maintaining a healthy environment in the workplace by ensuring an individual-technology fit and task-technology fit through training. This is in line with previous studies stating that employee professional-development opportunities are important for employees to maintain their job security [93]. By knowing the capabilities of the workforce, identifying the technological knowledge gap and eliminating these gaps through training, monitoring and feedback, employee security concerns can be mitigated.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, this can be countered by maintaining a healthy environment in the workplace by ensuring an individual-technology fit and task-technology fit through training. This is in line with previous studies stating that employee professional-development opportunities are important for employees to maintain their job security [93]. By knowing the capabilities of the workforce, identifying the technological knowledge gap and eliminating these gaps through training, monitoring and feedback, employee security concerns can be mitigated.…”
Section: Discussionsupporting
confidence: 89%
“…Expected benefits from the use of technology are that it motivates employees and creates a perception of ease of use and usefulness, as found in our study. As Lee, Park and Bakers [93] argue, in the present day competitive job market, employees must enhance skills and abilities to be of value to their employer, which is why the employees place more value on any learning opportunity that could enhance their competency. New technology introduced in the workplace is one such opportunity that brings benefits for employees and leads to satisfaction from learning achievement outcomes and job performance; as a result, bringing a perception of usefulness leading to intention to use of DSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In today's volatile, competitive markets, competition pushes organizations to change rapidly and innovate [55]. Various studies stress the specific importance of innovation in RL programs [30].…”
Section: The Moderating Role Of Organizational Innovativeness In the mentioning
confidence: 99%
“…The major skill enhancement programs in IT industry will plays a significant role for the enhancement of skills of employees in the organization.Zeinab Inanlou & Ji-Young Ahn [5] the outcome of the research showed that, employee communication, trust, positive organizational commitment, appreciation for innovativeness, employee participation in decision-making, employee training are the positive influencing aspects of employee performance in the organization. Jae Young Lee et al [6] organized a research study in the area of HRD practices, the top level management support, employee attitude; employee-employer relationship will plays significant results on job performance at work space. Even the results also evident that, the employee commitment and dedication will play a significant impact on work performance.…”
Section: Review Of Literaturementioning
confidence: 99%